Arkitektonisk kvalitet i vattennära läge : En fallstudie över Södra hamn, Luleå - Carlsson, Joakim; Johansson, Johan (2016)
In light of its positive population trend, the city of Luleå prepares room for more through the establishment of new settlements and densification of the downtown peninsula. This thesis aims to study and develop a 6.5 hectare area in the Södra Hamn area of Luleå. Through a literatary review designed to understand the processes and issues that can arise in an urban expansion an analysis was carried out using the method of Realistic City Analysis (Ellefsen & Tvilde, 1991). The analysis describes the city of Luleå’s historical development from its origins in the current Gammelstad Church Town and deals with factors that have been important for the city’s development. The results of the analysis are summarised along with observations from four different reference projects in a synthesis using the method of Problems seeking to articulate indicative objectives for the design proposal. The concept for the design proposal in Södra Hamn was developed through an iterative process where individual sketching was alternated with the results of the synthesis and theories discussed within the literary review. Based on the objective of becoming a part of the city and the guidelines from Luleå Vision 2050 the design proposal aims to propose a new establishment in the case study area. The proposal is considered to be the result of the thesis presenting an idea of how the case study area can be designed for this given goal. The proposal intends to offer variety and quality of experience by introducing a concept of how an urban structure can be divided and programmed to provide an alternating expression. By reshaping and enclosing the street space around the area new opportunities arose for the proposal to integrate into the surrounding cityscape. The proposed settlement is considered to be urban in its expression, density and with the type of activities proposed in the area. The design proposal exposes the water which is considered to be one of the city’s most important and valuable qualities. The design proposes a public ...